South caucasus and a 'New Great Game': the communication of competition in securitised international relations. Issue 2 (3rd April 2021) - Sadiyev Saleh, Sadi; Nasirov Khudam, Elman; Iskandarov Ibrahim, Khayal; Simons, Greg
ABSTRACT: This article seeks to compare and analyse the historical and contemporary arguments concerning the existence of the brand the 'Great Game' in Central Asia with that of a 'new' Great Game in the South Caucasus, while assessing the validity and problems of using this term. The article analyses the regional state of affairs and possible impacts of the Russian factor in forging close relations between South Caucasus states and NATO. It is argued that Russia's and NATO's vested interests in the region rhetorically contribute to European security system in the context of the security environment after the Georgian-Russian War of 2008 and its repercussions. NATO's presence may be interpreted as counterbalancing the Russian military presence in the region, but there are also clear limits to the alliance's willingness to actively engage in the region, not least the reluctance to antagonize Moscow. The context of geopolitical competition may be interpreted as a 'new' Great Game sharing similarities with nineteenth century competition of great powers, yet a number of clear differences also exist relative to the traditional Great Game.